Sacrificial Templating Fabrication of Hierarchically Porous Nitrogen‐Doped Carbon Nanosheets as Superior Oxygen Reduction Electrocatalysts. Issue 2 (10th January 2017) - Huang, Tao; Yang, Chongqing; Wang, Xinjing; Qiu, Feng; Jing, Fan; Jiang, Jianzhong; Liu, Ruili; Han, Sheng; Wu, Dongqing
Abstract: An unprecedented sacrificial templating strategy towards hierarchically porous N‐doped carbon nanosheets (PNC‐A) proceeds by the thermal treatment of the graphene hybrid coated with polyaniline‐encapsulated tin oxide nanoparticles, and the following etching process with acid and NH3 . The resultant PNC‐A exhibits well‐defined 2D morphology, high ratio of graphitic N and pyridinic N atoms as the active sites, and hierarchically porous structures with high specific surface area. Serving as the electrocatalyst for oxygen reduction reaction (ORR) in basic media, PNC‐A exhibits excellent catalytic activity via a four‐electron pathway with half‐wave potentials of 0.76 V vs. RHE electrode in alkaline media; the diffusion‐limiting current density is 5.48 mA cm −2, which is superior to most of the reported metal‐free ORR catalysts and comparable to state‐of‐the‐art Pt/C. Abstract : Ready ORR not : A sacrificial templating strategy yields hierarchically porous N‐doped carbon nanosheets (PNC‐A) with well‐defined 2D morphology. Their high ratio of graphitic N and pyridinic N atoms as the active sites and their hierarchically porous structures with high specific surface area result in an excellent catalytic activity toward oxygen reduction reaction in basic media.